Patterns of West Nile virus vector co-occurrence and spatial overlap with human cases across Europe - Shirin Taheri; Mikel Alexander González; María José Ruiz-López; Ramón Soriguer; Jordi Figuerola (One Health)
Its geographic range expansion and rising incidence make West Nile Virus (WNV) a major public health challenge in Europe. Although numerous studies have investigated geographic variation in WNV incidence in humans or equines, most have focused on climate and land-use factors; however, the implications of vector co-occurrence and niche overlap remain largely unexplored. Identifying areas where highly competent vectors overlap with favourable environmental conditions is crucial for determining areas at risk for future WNV outbreaks.We analysed the distribution and habitat suitability of four Culex mosquito vectors across Europe using an ensemble of six modelling techniques and relevant environmental variables. We generated probability maps, converted them into binary distribution maps through threshold-based methods, and weighted them by WNV vector competence to identify hotspots of vector co-occurrence and human cases.Our findings indicate that WNV vectors are unevenly distributed across Europe, with southern regions emerging as hotspots, particularly due to the presence of highly competent vectors such as Culex univittatus s.l., Culex modestus, and Culex pipiens. The overlap of Cx. modestus, Cx. torrentium, and Cx. pipiens in central, western, and eastern Europe indicates that competent WNV vectors are present in nearly all European regions. Among the environmental factors analysed, mean winter temperatures were the most influential, suggesting that mild winters could increase the distribution of WNV competent vectors. Our results also revealed a strong spatial overlap between hotspots of human WNV cases and vector co-occurrence, highlighting regions of elevated transmission risk.The high-risk hotspots identified in this large-scale study can guide local surveillance efforts and optimize resource allocation, ultimately enhancing the effectiveness of WNV surveillance.